Experimental study on effective stress coefficient of sandstone based on Mohr–Coulomb criterion under hydraulic-mechanical coupling - Wei Chen; Bowen Liu; Qiuhong Wu; Jie Liu; Zhenhua Ren; Qinyong Wang; Zhaofeng Liu; Wenqing Peng; Yu Zhou; Yuanzeng Wang; Zhili Peng (Scientific Reports)
Abstract Excavating water-saturated rock strata inevitably induces slippage and alters effective stress, significantly affecting the rock’s strength and deformation capacity. Understanding the hydro-mechanical coupling characteristics of these strata is essential for the safe excavation of vertical shafts. This study employs triaxial compression tests on water-saturated sandstone using the MTS-815 rock mechanics test system to investigate these characteristics. Tests were conducted at confining pressures (σ 3) of 10, 20, and 30 MPa, with pore water pressures set at 0%, 20%, 40%, 60%, and 80% of the respective confining pressures. The effective stress coefficient (α) was analyzed concerning the rock’s deformation and strength. A novel method for calculating the effective stress coefficient, based on the effective stress principle and the Mohr–Coulomb criterion, is proposed, leading to several key conclusions. The results indicate: (1) A positive linear correlation exists between the peak strength attenuation coefficient of sandstone specimens and the effective stress coefficient, with a correlation coefficient of 0.82. (2) The effective stress coefficient α is a bilinear function of pore water pressure p and volumetric stress Θ, with a fitting analysis correlation coefficient of 0.986. Furthermore, α is positively linearly correlated with p and negatively linearly correlated with Θ. (3) Under hydro-mechanical coupling, rock porosity is positively exponentially correlated with the effective stress coefficient. At constant confining pressure, the effective stress coefficient is positively linearly correlated with Poisson’s ratio and negatively linearly correlated with the elastic modulus. This criterion addresses the limitations of pore elasticity theory in determining the effective stress coefficient for the peak strength of rocks and significantly enhances the prediction of the mechanical properties of aquifer rocks.